An overview of Rattan distribution In four states In South-South part of Nigeria (2011)
Rattan, a non-timber resource in Nigeria's South-South forests remains largely unexplored. To create schedule for unlocking its potentials, this study investigates its availability, distribution and current utilization pattern in Akwa-Ibom, Bayelsa, Cross-rivers and Rivers States in Nigeria. Information was collected using structured questionnaire and on-the-spot-assessment while data was analyzed using simple statistical tools. The four states has rattan in abundance but unevenly distributed. Ten rattan species belonging to Lascopermas, Eremosphata and Calamus genera was identified in the study areas. Apart from Bayelsa State, its commercialization has begun insignificantly and without standard grading rule. The available products made from it are household items (70%) and furniture (30%). The estimates of unexploited rattan in Bayelsa and other three states are about 95% and 80% respectively. The traditional harvesting technique still subsists while users rarely treated harvested rattan. About 3.7m length of rattan costs about N30 as at December 2009. The study establishes that rattan resource is in abundance, unevenly distributed and yet to be appropriately commercialized in all the four states.